2006
DOI: 10.1121/1.2401198
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation of the underlying bone properties from mixed fast and slow mode ultrasonic signals

Abstract: We recently proposed that the observed apparent negative dispersion in bone can arise from the interference between fast wave and slow wave modes, each exhibiting positive dispersion [Marutyan et al., J. Acoust. Soc. Am. 120, EL55–EL61 (2006)]. In the current study, we applied Bayesian probability theory to solve the inverse problem: extracting the underlying properties of bone. Simulated mixed mode signals were analyzed using Bayesian probability. The calculations were implemented using the Markov chain Monte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…14,15,17 Previous work has demonstrated, however, that when decomposed, the fast wave and slow wave each exhibit positive dispersion. 19,27 Negative dispersion has been measured not only in trabecular bone [29][30][31][32][33] and cortical bone 34 in vitro but also in trabecular bone-mimicking phantoms. 35,36 Several models have been proposed that predict negative dispersion including multilayer models, 31,37 multiple scattering models, 38 and independent scattering models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,17 Previous work has demonstrated, however, that when decomposed, the fast wave and slow wave each exhibit positive dispersion. 19,27 Negative dispersion has been measured not only in trabecular bone [29][30][31][32][33] and cortical bone 34 in vitro but also in trabecular bone-mimicking phantoms. 35,36 Several models have been proposed that predict negative dispersion including multilayer models, 31,37 multiple scattering models, 38 and independent scattering models.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ability to separate the fast waves and slow waves is of considerable importance. Bayesian probability theory is one method for determining the individual properties of the interfering wave modes, 19,27 but in principle any method that can isolate the two waves could be applied. Wear, for example, recently demonstrated that the modified least squares Prony's method was also able to decompose a mixed-mode signal and yield accurate estimates of its ultrasonic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Solving the inverse problem-that is, reconstructing the ultrasonic properties of the interfering fast and slow waves-could provide more reliable information about the medium under study. Studies undertaken by Sebaa et al, 38 our Laboratory, [39][40][41][42] and Wear 43 have addressed various ways of addressing inverse problems in the ultrasonic investigation of cancellous bone to accomplish these goals. The objective of the current study is to extend and enhance our Laboratory's proposed technique of using Bayesian probability theory to recover the properties of individual interfering waves in data acquired on bone and bone-mimicking phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In previous work we proposed an alternative explanation of the observed negative dispersion and presented the results of numerical simulations demonstrating that negative dispersion can result from the interference of two propagating modes, each of which exhibits a positive dispersion, consistent with the Kramers-Kronig predictions. 10,11 The goal of the present study is to demonstrate this negative dispersion experimentally using the simplest example of a phantom that is capable of producing two such interfering waves. Most ultrasonic experimental data are acquired using phase sensitive piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%